Czas w modelowaniu zjawisk ekonomicznych - Mach, Maria Antonina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper is devoted to the problem of establishing a time structure adequate for economic phenomena modeling. It analyses modern economic environment as a domain for temporal modeling and representation, points out those features that justify the use of temporal logics for description and representation. To illustrate this, an example of barriers to entry has been chosen. To represent temporal phenomena properly, one has to choose an adequate time structure before performing the representational step. The reason is simple: time structure determines the representation way, and is strictly connected with the characteristics of the domain to be modeled. In the paper we presented a short survey of possible time structures, as well as the question of perceiving economic changes as a set of processes. We analysed economic environment's features in the temporal context and on this basis we proposed a time that is structure the most adequate and convenient for modeling economic phenomena. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 194-207